Utrzymanie pracowników w firmie a możliwości jej rozwoju - Baruk, Agnieszka Izabela (Retaining Employees in a Firm and Possibilities of its Development, 2007)
In the article, the problems of retaining employees in a firm were presented. The special attention was paid to reasons of seeking a new employer by Polish and foreign employees. Activities declared by employers to prevent these situations were described. The divergence between mentioned activities and employees' expectations was underlined too.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Marketing (3); 2007; nr 1171, s. 97-105